An examination of works for wind band: an english folk setting arranged by John Edmondson, a childhood hymn by David r. Holsinger, Mister Joe by Harold Bennet arranged by Larry Clark, and Celtic Air and Dance arranged by Michael Sweeney. - Lorenson, Zachary Steven (Kansas State University, 2011)
This report will present a detailed analysis of An English Folk Setting arranged by John Edmondson, A Childhood Hymn by David R. Holsinger, Mister Joe by Harold Bennett arranged by Larry Clark, and Celtic Air and Dance arranged by Michael Sweeney. The analyses are modeled on the “Teaching Music Through Performance in Band” series edited by Richard Miles, and the Macro-Micro-Macro score analysis form created by Dr. Frank Tracz. Chapter 2 will discuss the importance of music education as part of a well-rounded curriculum. Chapter 3 will discuss the importance of the use of quality literature, and how to determine if a piece of music is of high quality.
Keywords: Wind band; Music; Music (0413)